Online survey on existing sarcoidosis registries and biobanks: an ERN lung initiative. - D'alessandro, Miriana; Pianigiani, Tommaso; Bergantini, Laura; Cameli, Paolo; Bargagli, Elena; Balestro, Elisabetta; Börner, Eda; Bonella, Francesco (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
The present survey, promoted by the European Reference Network on rare respiratory diseases (ERN-Lung, Core Networks Sarcoidosis and ILD), aims to assess the existing sarcoidosis registries and biobanks across Europe and to compare the various types of biospecimen collected, the different procedures performed, and the sample storage conditions applied.This survey was initiated by the European Reference Network on rare respiratory diseases (ERN-Lung) Core Network “Sarcoidosis” in April 2023. The survey was launched by ERN-Lung Core Network “Sarcoidosis” in August 2023 and remained active until end of February 2024. It was disseminated to all ERN-Lung Core Network “Sarcoidosis” members (first round) and to “ILD” CN members (second round) via mail. Consent to completing the questionnaire was expressly requested before starting the online procedure. This survey raises important questions about future developments. The creation of registries and biobanks specific for sarcoidosis is mandatory to improve the knowledge of sarcoidosis pathogenesis and its management.This survey shows that the map of registries and biobanks specific for sarcoidosis in Europe is fragmented and needs merging, funding and coordination to allow high quality and structured research in sarcoidosis.